Du post-apocalyptique au posthumain - Anne-Sophie Hillard (Recherches Germaniques)
This paper analyzes the apocalyptic theme in two contemporary German SF-novels. Both stories plunge the reader into a distant future in which mankind as we know it has long since disappeared. In this sense, Dietmar Dath presents post-apocalyptic, or rather post-post-apocalyptic universes, for these stories tell about the end of several civilizations. However, the apocalypses at stake here are cleared of their fateful dimension; they are considered as turning points rather than as a real ending. In Dath’s Die Abschaffung der Arten (2008) the end of humankind enables the advent of a revolutionary posthumanity which consists in genetically altered animals called ‘Gente’ capable of shifting gender and species. Yet the Gente also experience an apocalypse of their own and there are several of them throughout the novel. This chain of ends of time emphasizes a conception of the apocalypse as evolution over a teleological understanding of history: there is no more myth of fall and redemption here. The novel Pulsarnacht (2012) depicts a world where different intelligent species live alongside each other. The Dims, enslaved by their masters, the Custai, and despised by the posthumans from Yasaka, keep telling the myth of the Night of Pulsars. According to them, the day will come when all the pulsar signals will turn off at the same time. This event, though physically impossible, will nonetheless occur and disrupt the existing order. The apocalypse of the Night of Pulsars can be conceived of as an actual revelation.